Hunting down the X17 boson at the CERN SPS; The European Physical Journal C; Vol. 80, iss. 12 - Depero E. Emanuele; Andreev Yu. M. Yury Mikhaylovich; Banerjee D.; Bernhard J. Johannes; Dusaev R. R. Renat Ramilyevich (2020, 2020)
Title screen